Flame-retardant communication power sheath pipe and preparation method thereof

A composite material using segmental copolymer polypropylene and high-density polyethylene with phosphazene-based retardants forms a dense carbon layer to enhance the flame retardancy and mechanical properties of communication power sheathings, addressing the limitations of existing PE and PP pipes.

CN119955195AActive Publication Date: 2025-05-09GUANGDONG YONGGAO PLASTIC INDUSTRY DEVELOPMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510129805.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-05
Publication Date
2025-05-09
Estimated Expiration
2045-02-05

AI Technical Summary

Technical Problem

PE and PP pipes used in communication power sheathings suffer from poor flame retardancy, and existing methods to enhance their flame retardance, such as using brominated or non-halogen compounds, either harm the environment, require high dosages, or compromise mechanical properties.

Method used

A composite material comprising segmental copolymer polypropylene, high-density polyethylene, and a blend of phosphazene-based flame retardants, along with additives like compatibilizers and nanoclay, to form a dense carbon layer that inhibits flame spread and enhances mechanical properties.

Benefits of technology

The composite material achieves high flame retardancy, maintaining mechanical strength and flexibility, while forming a stable carbon layer that suppresses fire propagation and improves oxygen index.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005261164970000101
    Figure BDA0005261164970000101
  • Figure BDA0005261164970000111
    Figure BDA0005261164970000111
Patent Text Reader

Abstract

The invention discloses a flame-retardant communication power sheath pipe and a preparation method thereof, and belongs to the technical field of sheath pipes. The flame-retardant communication power sheath pipe comprises the following raw materials in parts by mass: 15-40 parts of block co-polypropylene, 20-50 parts of high-density polyethylene, 0-10 parts of heat-resistant polyethylene, 25-35 parts of compound flame-retardant powder, 0.1-1 part of a compatilizer, 0.1-0.8 part of an antioxidant, 1-3 parts of a coupling agent and 0.5-2 parts of a dispersing agent, wherein the compound flame-retardant powder comprises piperazine pyrophosphate and / or melamine polyphosphate. Block co-polypropylene and high-density polyethylene are blended, the loss of tensile yield strength caused by excessive powder can be made up, formation of a carbon layer can be better promoted, heat-resistant polyethylene can form an interpenetrating structure between molecular networks formed by the composite material, the compactness of the composite material is effectively improved, and the service life of the composite material is prolonged. Therefore, the oxygen index of the composite material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sheath pipes, and in particular relates to a flame-retardant communication power sheath pipe and a preparation method thereof. Background Art

[0002] Communication power sheath pipe is an external structure used to protect cables. It is made of a variety of materials and has the functions of insulation, protection and fixing cables. This sheath pipe is widely used in the fields of power and communication to ensure the safety and reliability of cables in various environments.

[0003] Existing communication power sheath pipes are mostly plastic pipes, among which PVC (polyvinyl chloride) pipes are the main ones. However, compared with PVC pipes, PE (polyethylene) pipes and PP (polypropylene) pipes have better performance, such as corrosion resistance, good flexibility and low temperature resistance. In actual application, they have the advantages of long service life, low production energy consumption, small water flow resistance, easy installation and disassembly, etc., and are expected to replace PVC pipes and become a more widely used pipe material. At present, high-density polyethylene pipes have been widely used in communication power protection pipes, and have become one of the materials that is difficult to replace PVC pipes in the trenchless field.

[0004] However, when PE pipes and PP pipes are used as communication power sheath pipes, there is a problem of poor flame retardancy. Since polyethylene and polypropylene materials are flammable polymers with a low oxygen index, the pipes prepared using polyethylene and polypropylene generally have poor flame retardancy. In order to improve their safety as communication power sheath pipes, their flame retardancy must be improved.

[0005] At present, the method to improve the flame retardant properties of PP pipes and PE pipes is to add bromine-based composite flame retardants or halogen-free flame retardants during the preparation process. Bromine-based flame retardants are not environmentally friendly and are relatively toxic, while halogen-free flame retardants need to be added in large amounts to achieve a certain flame retardant effect. Moreover, the flame retardant grade is not high and it is difficult to reach V0 level. In addition, the addition of a large amount of halogen-free flame retardants significantly reduces the mechanical properties of the resulting pipes, which cannot meet the application of pipes in trenchless fields. Summary of the invention

[0006] The purpose of the present invention is to provide a flame-retardant communication power sheath pipe and a preparation method thereof, so as to solve the problem that polyolefin pipes have poor flame retardancy and it is difficult to balance flame retardancy and mechanical properties.

[0007] The purpose of the present invention can be achieved through the following technical solutions:

[0008] In a first aspect, the present invention provides a flame-retardant communication power sheath pipe, comprising the following raw materials in parts by weight:

[0009] 15-40 parts of block copolymer polypropylene;

[0010] 20-50 parts of high-density polyethylene;

[0011] Heat-resistant polyethylene 0-10 parts;

[0012] Compound flame retardant powder 25-35 parts;

[0013] Compatibilizer 0.1-1 part;

[0014] 0.1-0.8 parts of antioxidant;

[0015] 1 to 3 parts of coupling agent;

[0016] Dispersant 0.5-2 parts;

[0017] The composite flame retardant powder comprises piperazine pyrophosphate and / or melamine polyphosphate.

[0018] Preferably, the block copolymer polypropylene has a melt index of ≤0.8 g / 10 min, a tensile yield strength of ≥25 MPa, and a flexural modulus of ≥1500 MPa.

[0019] Preferably, the compatibilizer includes a combination of one or more of SEBS grafted maleic anhydride, PP grafted maleic anhydride and PE grafted maleic anhydride.

[0020] Preferably, the antioxidant includes a combination of one or more of antioxidant 1010 , antioxidant 1076 , antioxidant 168 , antioxidant 245 , antioxidant 1098 and antioxidant 626 .

[0021] Preferably, the coupling agent includes any one of a silane coupling agent and a titanate coupling agent.

[0022] More preferably, the silane coupling agent includes a combination of one or more of γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, γ-methacrylatepropyltrimethoxysilane and N-(2-aminoethyl)-3-aminopropyltriethoxysilane.

[0023] More preferably, the titanate coupling agent includes a combination of one or more of isopropyl tri(dodecylbenzenesulfonyl) titanate, isopropyl triisostearate titanate, and isopropyl tri(dioctylpyrophosphate) titanate.

[0024] Preferably, the dispersant includes a combination of one or more of polyethylene wax, calcium stearate, zinc stearate, butyl stearate and vinyl bisstearamide.

[0025] By adopting the above technical scheme, the present invention selects piperazine pyrophosphate and / or melamine polyphosphate as the main flame retardant components of the present invention. Piperazine pyrophosphate and melamine polyphosphate can promote carbonization reaction at high temperature to generate a dense carbon layer covering the polymer surface, and when heated, high temperature decomposition produces gas, so that the formed carbon layer expands rapidly, thereby isolating oxygen and heat, and as a physical barrier, it can further reduce the temperature of the material surface, reduce the volatilization of combustible gas, and finally extinguish the flame. The piperazine part in piperazine pyrophosphate can also capture active free radicals during the combustion process, interrupt the combustion chain reaction, and reduce the combustion speed, which is very important for slowing down the spread of flames.

[0026] However, like many halogen-free flame retardants, piperazine pyrophosphate and melamine polyphosphate must be added in sufficient amounts to achieve a good flame retardant effect, and excessive addition will inevitably lead to a significant decrease in the mechanical properties of the material. In order to improve this problem, the present invention uses block copolymer polypropylene and high-density polyethylene for compounding, wherein the block copolymer polypropylene contains a higher proportion of ethylene components than homopolymer polypropylene and has better impact resistance while maintaining a certain degree of rigidity, and the high-density polyethylene has excellent flexibility. The combination of the two can significantly improve the impact strength and elongation at break of the composite material, thereby compensating for the loss of tensile yield strength caused by excessive flame retardant powder.

[0027] Moreover, high-density polyethylene has high thermal stability and can maintain good physical and chemical properties at high temperatures, which promotes the improvement of the overall flame retardant properties of the material. The blending of block copolymer polypropylene and high-density polyethylene can help disperse the compound flame retardant powder and promote the formation of a more uniform carbon layer, further improving the flame retardant properties and oxygen index of the material.

[0028] In order to improve the compatibility between block copolymer polypropylene and high-density polyethylene, a compatibilizer is also added to the system. The introduction of the compatibilizer can reduce the interfacial tension, so that the two polymers can interact better, thereby optimizing the dispersion of the compound flame-retardant powder in the system. A good dispersion state can improve the mechanical properties of the material. In order to further improve the interfacial effect between the polymer and the compound flame-retardant powder, a coupling agent is also added. The coupling agent can effectively reduce the agglomeration phenomenon between the powders, so that the obtained composite material has a uniform microstructure, which can better disperse stress and improve the mechanical properties of the material. Moreover, the addition of a coupling agent can promote the formation of a carbon layer during combustion, help isolate oxygen, prevent the spread of flames, slow down the rate of temperature rise, further improve the flame retardant properties of the material, and finally obtain a pipe material with excellent comprehensive performance.

[0029] Preferably, the compound flame retardant powder further comprises a flame retardant synergist; the flame retardant synergist comprises a combination of one or more of diethyl aluminum hypophosphite, inorganic aluminum hypophosphite and pentaerythritol.

[0030] Preferably, the added amount of the flame retardant synergist is 1 to 3% of the total mass of the compounded flame retardant powder.

[0031] By adopting the above technical scheme, in order to further improve the flame retardant properties of the composite material, the compound flame retardant powder also includes a flame retardant synergist, which can decompose non-flammable gases at the beginning of combustion and form a flame retardant layer to protect the substrate from more severe pyrolysis. It can also increase the mass and density of the carbon layer formed by the flame retardant, provide additional heat resistance and anti-dripping performance, produce a synergistic effect, form a more effective flame retardant system, and achieve better flame retardant standards.

[0032] Preferably, the heat-resistant polyethylene includes a combination of one or more of an ethylene-1-butene copolymer, an ethylene-1-hexene copolymer and an ethylene-octene copolymer.

[0033] More preferably, the mass fraction of the heat-resistant polyethylene is 6 to 9 parts.

[0034] By adopting the above technical scheme, in order to further improve the flame retardant properties and mechanical properties of the composite material, the present invention also adds heat-resistant polyethylene to the composite material. Specifically, the heat-resistant polyethylene is a random copolymer composed of ethylene and high-carbon α-olefins such as butene, hexene and octene, which contains a certain proportion of long-chain branched structures, and can form a mixture of semi-crystalline regions and non-crystalline regions at the microscopic level, which can help improve the flexibility of the material while improving the strength, and can maintain certain physical properties at high temperatures. Moreover, when high-carbon α-olefins are introduced into the ethylene main chain as comonomers, longer side chain branches will be formed, which can help increase the entanglement density between molecules, and can maintain a relatively stable shape even in a high temperature environment, and has good heat resistance.

[0035] This structural feature can form a microphase separation structure in the composite material, which can effectively disperse stress and improve the mechanical properties of the material. In addition, copolymerization with ethylene can also improve its compatibility in the material system of the present invention and increase the interfacial force.

[0036] Moreover, the addition of heat-resistant polyethylene can form an interlaced structure between the molecular networks formed by the block copolymer polypropylene and high-density polyethylene composites, and its crystalline part can produce a certain interaction with the polyethylene and polypropylene matrices, thereby effectively improving the density of the composites and effectively improving the oxygen index of the composites. The presence of heat-resistant polyethylene also helps to promote the formation of a denser and more stable carbon layer under heating conditions, helping to isolate flames and oxygen, reduce heat transfer, and effectively inhibit the spread of fire, thereby improving the flame retardant properties of the composites.

[0037] Preferably, the raw material also includes 3 to 5 parts by mass of microcrystalline layered muscovite.

[0038] Preferably, the particle size of the microcrystalline layered muscovite is 400-600 mesh.

[0039] By adopting the above technical scheme, the tensile yield strength loss caused by the compound flame retardant powder can be effectively compensated under the compounding effect of block copolymer polypropylene and high-density polyethylene, but the effect of improving the oxygen index of the composite material is limited. Moreover, piperazine pyrophosphate, as the main component of the compound flame retardant powder, is a highly polar compound and is easily hydrolyzed. It is also easy to precipitate during the molding process, thereby affecting the flame retardancy of the material.

[0040] In order to further improve the performance of the material, microcrystalline layered muscovite is also added to the composite material. The coupling agent and compatibilizer in the composite material can also help the microcrystalline layered muscovite to be evenly dispersed in the composite material, so that one or more layers of nano-level lamellar structures can be formed inside the composite material of polypropylene and polyethylene. These lamellar structures can effectively hinder the transfer path of oxygen, heat and combustible gas inside the material, thereby slowing down the spread of flames and improving the overall oxygen index of the material. In addition, the aluminosilicate component in the microcrystalline layered muscovite can play a certain catalytic role in high temperature environments, helping to generate more non-combustible carbon residues, helping to build a denser and more stable carbon layer, and increasing the flame retardancy of the material.

[0041] The nanoscale physical barrier formed by the microcrystalline layered muscovite in the composite material can also directly reduce the chance of moisture contacting the compounded flame retardant powder, effectively preventing moisture intrusion, thereby reducing the risk of hydrolysis. In addition, the metal cations contained in the microcrystalline layered muscovite will interact with piperazine pyrophosphate, thereby improving the stability of the compounded flame retardant powder through electrostatic attraction and chemical bonding, thereby improving the hydrolysis resistance of the composite material.

[0042] In addition, the addition of microcrystalline layered muscovite can help maintain and enhance the mechanical properties of the material, improve processability, and make the material easier to shape.

[0043] In a second aspect, the present invention provides a method for preparing a flame-retardant communication power sheath pipe, comprising the following process steps:

[0044] S1. Add dispersant and coupling agent to the compound flame retardant powder in sequence, mix well, add block copolymer polypropylene and high-density polyethylene, stir and mix to obtain a premix;

[0045] S2. Add a compatibilizer, microcrystalline layered muscovite and heat-resistant polyethylene to the premix in sequence, stir and mix, and then obtain a flame-retardant communication power sheath pipe through melt extrusion, cooling and shaping, and pulling and cutting.

[0046] Preferably, the technical problem of the present invention can be solved without adding microcrystalline layered muscovite in step S2.

[0047] Preferably, in step S1, the premix is ​​first melted and extruded to obtain a premix masterbatch, and then the premix masterbatch is stirred and mixed with a compatibilizer, microcrystalline layered muscovite and heat-resistant polyethylene, and then melt-extruded, cooled, shaped and pulled and cut to obtain a flame-retardant communication power sheath pipe.

[0048] By adopting the above technical solution, in order to further improve the dispersibility between the compound flame retardant powder and the polymer substrate, during the preparation process, part of the polymer and the compound flame retardant powder can be mixed first, and then mixed with the remaining materials after making a masterbatch and extruded. This is not only beneficial for processing but also for improving material performance.

[0049] Beneficial effects of the present invention:

[0050] 1. The flame-retardant communication power sheath pipe of the present invention, in order to improve the mechanical properties of the high-addition flame-retardant powder system, adopts the method of blending block copolymer polypropylene and high-density polyethylene, while maintaining good rigidity, improving the impact resistance of the material, compensating for the loss of tensile yield strength caused by excessive powder, and can also better promote the formation of carbon layer, improve the flame retardant properties and oxygen index of the material. On this basis, in order to further improve the performance of the material, heat-resistant polyethylene is also added to the composite material, which can form an interlaced structure between the molecular network formed by the block copolymer polypropylene and high-density polyethylene composite material, and its crystalline part can produce a certain interaction with the polyethylene and polypropylene matrix, thereby effectively improving the density of the composite material and effectively improving the oxygen index of the composite material.

[0051] 2. Microcrystalline layered muscovite is also added to the flame-retardant communication power sheath pipe of the present invention, which can form one or more layers of nano-level lamellar structures inside the composite material of polypropylene and polyethylene. These lamellar structures can effectively block the transfer path of oxygen, heat and combustible gas inside the material, improve the oxygen index of the material, and can also effectively prevent moisture intrusion, reduce the problems of hydrolysis and easy precipitation of compound flame-retardant powders, and finally help maintain and enhance the mechanical properties of the material, improve the processability, and make the material easier to shape. DETAILED DESCRIPTION

[0052] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] Example

[0054] Example 1, a flame retardant communication power sheath pipe, is prepared according to the following process steps:

[0055] S1. 0.1 kg of calcium stearate, 0.05 kg of antioxidant 1010 and 0.2 kg of γ-aminopropyl triethoxysilane were added to 3 kg of compound flame retardant powder, wherein the compound flame retardant powder comprises a mixture of 98% of piperazine pyrophosphate and melamine polyphosphate and 2% of diethyl aluminum hypophosphite, the mass ratio of piperazine pyrophosphate to melamine polyphosphate is 2:1, and after mixing evenly, 2.5 kg of block copolymer polypropylene (melt index is 0.6 g / 10 min) and 3.2 kg of high-density polyethylene (melt index is 30 g / 10 min) were added, and the mixture was stirred to obtain a premix;

[0056] S2. 0.1 kg of SEBS grafted maleic anhydride and 0.8 kg of ethylene-1-butene copolymer were added to the premix in sequence, and after stirring and mixing, the mixture was melt-extruded, cooled and shaped, and then pulled and cut to obtain a flame-retardant communication power sheath pipe.

[0057] Embodiments 2 to 4 are flame-retardant communication power sheath pipes, which differ from Embodiment 1 only in that the raw material ratio is adjusted, as shown in Table 1:

[0058] Table 1 Formula table of Example 1 to Example 4

[0059] Example 1 Example 2 Example 3 Example 4 Block copolymer polypropylene / kg 2.5 1.5 3.5 2.0 High density polyethylene / kg 3.2 4.0 2.2 4.0 Ethylene-1-butene copolymer / kg 0.8 / 0.8 0.7 Compound flame retardant powder / kg 3.0 3.0 3.0 2.7 SEBS grafted maleic anhydride / kg 0.1 0.1 0.1 0.1 Antioxidant 1010 / kg 0.05 0.05 0.05 0.05 γ-Aminopropyltriethoxysilane / kg 0.2 0.2 0.25 0.15 Calcium stearate / kg 0.1 0.1 0.1 0.1

[0060] The composite flame retardant powders in Examples 2 to 4 are all a mixture of 98% piperazine pyrophosphate and melamine polyphosphate and 2% diethyl aluminum hypophosphite, wherein the mass ratio of piperazine pyrophosphate to melamine polyphosphate is 2:1.

[0061] Example 5, a flame retardant communication power sheath pipe, is different from Example 1 only in that the compound flame retardant powder is 98% piperazine pyrophosphate and 2% diethyl aluminum hypophosphite.

[0062] Example 6, a flame retardant communication power sheath pipe, is different from Example 1 only in that the compound flame retardant powder is 98% melamine polyphosphate and 2% diethyl aluminum hypophosphite.

[0063] Example 7, a flame-retardant communication power sheath pipe, is different from Example 1 only in that γ-aminopropyl triethoxysilane is replaced by an equal amount of isopropyl tri(dodecylbenzenesulfonyl) titanate.

[0064] Example 8, a flame-retardant communication power sheath pipe, is different from Example 1 only in that an equal amount of ethylene-1-octene copolymer is used to replace ethylene-1-butene copolymer.

[0065] Example 9, a flame-retardant communication power sheath pipe, is prepared according to the following process steps:

[0066] S1. 0.1 kg of calcium stearate, 0.05 kg of antioxidant 1010 and 0.2 kg of γ-aminopropyl triethoxysilane were added to 3 kg of compound flame retardant powder, wherein the compound flame retardant powder comprises a mixture of 98% of piperazine pyrophosphate and melamine polyphosphate and 2% of diethyl aluminum hypophosphite, the mass ratio of piperazine pyrophosphate to melamine polyphosphate is 2:1, after mixing evenly, 2.5 kg of block copolymer polypropylene (melt index is 0.6 g / 10 min) and 3.2 kg of high-density polyethylene (melt index is 30 g / 10 min) were added, stirred and mixed to obtain a premix, and the premix was melt-extruded and granulated to obtain a premix masterbatch;

[0067] S2. 0.1 kg of SEBS grafted maleic anhydride and 0.8 kg of ethylene-1-butene copolymer were added to the premix masterbatch in sequence, stirred and mixed, and then melt-extruded, cooled and shaped, and then pulled and cut to obtain a flame-retardant communication power sheath pipe.

[0068] Example 10, a flame-retardant communication power sheath pipe, is different from Example 1 only in that the compound flame-retardant powder is a mixture of piperazine pyrophosphate and melamine polyphosphate, and the mass ratio of piperazine pyrophosphate to melamine polyphosphate is 2:1.

[0069] Example 11, a flame-retardant communication power sheath pipe, is different from Example 1 only in that 0.4 kg of microcrystalline layered muscovite (with an average particle size of 400 mesh) is further added in step S2.

[0070] Example 12, a flame-retardant communication power sheath pipe, is different from Example 11 only in that the added amount of microcrystalline layered muscovite is 0.3 kg.

[0071] Example 13, a flame-retardant communication power sheath pipe, is different from Example 11 only in that the added amount of microcrystalline layered muscovite is 0.5 kg.

[0072] Example 14, a flame-retardant communication power sheath pipe, is different from Example 11 only in that the added amount of microcrystalline layered muscovite is 0.1 kg.

[0073] Example 15, a flame-retardant communication power sheath pipe, is different from Example 11 only in that the added amount of microcrystalline layered muscovite is 0.7 kg.

[0074] Example 16, a flame-retardant communication power sheath pipe, differs from Example 11 only in that the microcrystalline layered muscovite is replaced with an equal amount of muscovite with an average particle size of 800 mesh.

[0075] Comparative Example

[0076] Comparative Example 1 is a flame-retardant communication power sheath pipe, which is different from Example 1 only in that the block copolymer polypropylene is replaced by an equal amount of homopolymer polypropylene.

[0077] Comparative Example 2 is a flame-retardant communication power sheath pipe, which is different from Example 1 only in that an equal amount of medium-density polyethylene is used to replace high-density polyethylene.

[0078] Comparative Example 3, a flame-retardant communication power sheath pipe, is different from Example 1 only in that the added amount of ethylene-1-butene copolymer is 1.2 kg.

[0079] Performance testing

[0080] 1. Flame retardant performance test:

[0081] (1) Flame retardant grade: According to the relevant records in GB / T 2408-2021 "Determination of combustion performance of plastics - Horizontal and vertical methods", the vertical combustion flame retardant grade of the flame-retardant communication power sheath pipe obtained in the embodiment and the comparative example was tested.

[0082] (2) Oxygen index: According to the relevant records in GB / T 2406.2-2009 "Determination of combustion behavior of plastics by oxygen index method Part 2: Room temperature test", the oxygen index of the flame-retardant communication power sheathing pipe obtained in the examples and comparative examples was tested.

[0083] 2. Mechanical properties test: According to the relevant records in GB / T 1040.1-2018 "Determination of tensile properties of plastics Part 1: General", the tensile yield strength and elongation at break of the flame-retardant communication power sheath pipe obtained in the embodiment and the comparative example were tested.

[0084] The above test results are shown in Table 2:

[0085] Table 2 Performance test results

[0086]

[0087]

[0088] According to Table 2, in combination with Example 1 and Example 9, it can be seen that the mechanical properties of Example 9 are slightly improved compared with Example 1. The reason is that in Example 9, a two-step method is adopted for preparation, firstly melt extrusion is used to obtain a premix masterbatch, and then the premix masterbatch is mixed with other components and extruded. The composite material obtained in this way has better dispersibility and can improve the mechanical properties of the material to a certain extent.

[0089] Combining Example 1 and Example 10, it can be seen that the flame retardant level of Example 10 decreases. The reason is that no flame retardant synergist is added to the compound flame retardant powder in Example 10, which will increase the impact of pyrolysis on the substrate in the early stage of heating, and cannot help the flame retardant to improve the quality and density of the formed charcoal layer, and cannot produce a synergistic effect, thereby resulting in a decrease in flame retardant performance.

[0090] Combining Example 1 and Example 11, it can be seen that the oxygen index and tensile yield strength of Example 11 are increased compared with Example 1. The reason is that the only difference between Example 11 and Example 1 is that microcrystalline layered muscovite is added. The addition of microcrystalline layered muscovite can form one or more layers of nano-level lamellar structure inside the material, which can effectively hinder the transfer path of oxygen, heat and combustible gas inside the material, improve the oxygen index of the material, and can also effectively prevent moisture intrusion, reduce the problems of hydrolysis and easy precipitation of compound flame retardant powder, and effectively maintain and improve the mechanical properties of the material.

[0091] Combining Example 11 and Example 16, it can be seen that the oxygen index and tensile yield strength of Example 16 are lower than those of Example 11. The reason is that the muscovite added in Example 16 has a large particle size, its dispersibility in the material is reduced, and its specific surface area is significantly reduced, which can easily cause debonding, thereby reducing the mechanical properties of the material.

[0092] Combining Example 1, Comparative Example 1 and Comparative Example 2, it can be seen that the flame retardant properties and mechanical properties of Comparative Example 1 and Comparative Example 2 are lower than those of Example 1. The reason is that block copolymer polypropylene is not used in Comparative Example 1, and high-density polyethylene is not used in Comparative Example 2. The impact strength of homopolymer polypropylene is lower than that of block copolymer polypropylene, and it is difficult to form an intermolecular entanglement structure with polyethylene, resulting in a decrease in the density of the material, thereby resulting in a decrease in the performance of the obtained composite material; the medium-density polyethylene has a decrease in flexibility and strength compared to high-density polyethylene, and it is difficult to make up for the loss of tensile yield strength caused by excessive flame retardant powder.

[0093] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A flame-retardant communication power sheath pipe, characterized in that: Including the following raw materials by mass: 15-40 parts of block copolymer polypropylene; 20-50 parts of high-density polyethylene; Heat-resistant polyethylene 0-10 parts; Compound flame retardant powder 25-35 parts; Compatibilizer 0.1-1 part; 0.1-0.8 parts of antioxidant; 1 to 3 parts of coupling agent; Dispersant 0.5-2 parts; The composite flame retardant powder comprises piperazine pyrophosphate and / or melamine polyphosphate.

2. The flame-retardant communication power sheath pipe according to claim 1, characterized in that: The compound flame retardant powder further comprises a flame retardant synergist; the flame retardant synergist comprises a combination of one or more of diethyl aluminum hypophosphite, inorganic aluminum hypophosphite and pentaerythritol.

3. The flame-retardant communication power sheath pipe according to claim 2, characterized in that: The added amount of the flame retardant synergist is 1-3% of the total mass of the compound flame retardant powder.

4. The flame-retardant communication power sheath pipe according to claim 1, characterized in that: The heat-resistant polyethylene includes a combination of one or more of an ethylene-1-butene copolymer, an ethylene-1-hexene copolymer and an ethylene-octene copolymer.

5. The flame-retardant communication power sheath pipe according to claim 1, characterized in that: The mass fraction of the heat-resistant polyethylene is 6 to 9 parts.

6. The flame-retardant communication power sheath pipe according to claim 1, characterized in that: The raw materials also include 3 to 5 parts by mass of microcrystalline layered muscovite.

7. The flame-retardant communication power sheath pipe according to claim 1, characterized in that: The particle size of the microcrystalline layered muscovite is 400-600 meshes.

8. The flame-retardant communication power sheath pipe according to claim 1, characterized in that: The coupling agent includes any one of a silane coupling agent and a titanate coupling agent.

9. The flame-retardant communication power sheath pipe according to claim 1, characterized in that: The compatibilizer includes one or more combinations of SEBS grafted maleic anhydride, PP grafted maleic anhydride and PE grafted maleic anhydride.

10. A method for preparing a flame-retardant communication power sheath pipe according to any one of claims 1 to 9, characterized in that: The process steps include: S1. Add dispersant and coupling agent to the compound flame retardant powder in sequence, mix well, add block copolymer polypropylene and high-density polyethylene, stir and mix to obtain a premix; S2. Add a compatibilizer, microcrystalline layered muscovite and heat-resistant polyethylene to the premix in sequence, stir and mix, and then obtain a flame-retardant communication power sheath pipe through melt extrusion, cooling and shaping, and pulling and cutting.

Citation Information

Patent Citations

  • Special V0-grade halogen-free flame-retardant polypropylene material for extrusion blistering and preparation method of polypropylene material

    CN109705462A

  • Composition and fire-retardant resin composition

    CN111433326A

  • Multi-block or random copolymerized halogen-free flame-retardant macromolecule and flame-retardant polyolefin material thereof

    CN114181397A

  • Polypropylene composite material for cable sheath and preparation method thereof

    CN117511110A